Transport from the wild rapidly alters the diversity and composition of skin microbial communities and antifungal taxa in spring peeper frogs - Kane, Lauren P.; Van Bonn, William G.; Oliaro, Francis J.; Edwardson, Christian F.; Smith, Malissa; Pinnell, Lee J. (Frontiers in Microbiomes, 2024)
Amphibians are routinely collected from the wild and added into managed care and public display facilities; however, there is a gap in understanding how these practices might alter the diversity and composition of skin microbial communities on these animals. The aim of this study was to evaluate and compare skin microbial communities of spring peeper frogs (Pseudacris crucifer) from acquisition in the wild through the end of their quarantine period and identify microbial taxa with antifungal properties.From an original group of seventy-six frogs, cohorts of ten were swabbed when acquired in the wild, upon transport from the wild, and swabbed throughout a 9-week quarantine period while under managed care. An immediate loss of microbial richness and diversity was evident upon transfer of the frogs from their original environment and continued throughout subsequent sampling time-points during quarantine. Importantly, antifungal taxa comprised significantly more of the overall skin community after the frogs were moved from the wild, largely due to members of the family Moraxellaceae. Overall, our findings demonstrate that amphibian skin microbiome changes immediately on removal from the wild, and that these changes persist throughout quarantine while being housed under managed care. This may play a pivotal role in the development of dermatological disease and have implications in the health and immune function of amphibians.